Association of Chromosomal RNA with Repetitive DNA - Sivolap, Yuriy M. (1971)
Chromosomal RNA, which is a component of the chromosomes of higher organisms, and whose participation is required for sequence-specific interaction of chromosomal proteins with chromosomal DNA, occurs in chromosomes bound to DNA. We have found that the DNA sequences to which chromosomal RNA binds are repetitive ones.